The Inverse Association of Muscular Strength with Carotid Intima-media and Extra-media Thickness in Women - Karabinus, Julie A.; DeBlois, Jacob P.; Keller, Allison; Glasgow, Alaina C.; Barreira, Tiago V.; Heffernan, Kevin S. (International Journal of Sports Medicine, 2020)
The purpose of this study was to determine the relationship between strength and atherosclerotic cardiovascular disease (CVD) risk in young women. Carotid intima-media thickness (IMT) and extra-media thickness (EMT) were used as measures of subclinical atherosclerosis and CVD risk. Muscular strength, IMT, and EMT were measured in 70 young women (mean age=21±4 years). Strength was determined using a handgrip dynamometer and expressed relative to body mass. IMT and EMT were measured using ultrasonography of the left common carotid artery. Objectively measured moderate-vigorous physical activity (MVPA) was assessed with accelerometry. Higher relative handgrip strength was associated with lower IMT (r=−0.23; p<0.05) and lower EMT (r=−0.27; p<0.05). Associations between relative handgrip strength and IMT (r=−0.24) as well as EMT (r=−0.25) remained significant after adjusting for potential confounders including traditional CVD risk factors and MVPA (p<0.05). These results show that there is an inverse association between handgrip strength with carotid IMT and EMT in young women. Muscular strength may reduce CVD risk in young women via favorable effects on subclinical carotid atherosclerosis independent of physical activity.
Keywords: muscular strength; handgrip; carotid artery; atherosclerosis